INFLUENCE OF THIRD-PARTY FUNDS, CAR, NPF AND FDR TOWARDS THE RETURN ON ASSETS OF ISLAMIC BANKS IN INDONESIA - Risma Ayu Kinanti; Purwohandoko Purwohandoko (University of Islam Malang, 2017)
The purpose of this research is to analyze the influence of third party funds, capital adequacy ratio (CAR), non performing financing (NPF) ,financing to deposit ratio (FDR) Of return on assets (ROA) during period of 2008-2013 syariah banks in indonesia. About 3 syariah banks in indonesia was taken as sample for this research. The data used for this research were obtained from the data of Quarterly Published Financial Report Period 2008 up to 2013. The analysis technique used is Linear Regression that aims for estimating the relationships among variables. The results of F test showing that Third Party Funds, CAR, NPF and FDR simultaneously influential to ROA. While The result of t-test showing Third Party and NPF has significant positif effect to ROA, CAR and FDR has a negative effect on ROA syariah banks in Indonesia.